Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/term.3288
|View full text |Cite
|
Sign up to set email alerts
|

Guiding bone formation using semi‐onlay calcium phosphate implants in an ovine calvarial model

Abstract: The restoration of cranio‐maxillofacial deformities often requires complex reconstructive surgery in a challenging anatomical region, with abnormal soft tissue structures and bony deficits. In this proof‐of‐concept, the possibility of vertical bone augmentation was explored by suspending hemispherically shaped titanium‐reinforced porous calcium phosphate (CaP) implants (n = 12) over the frontal bone in a sheep model (n = 6). The animals were euthanized after week 13 and the specimens were subject to micro‐comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 48 publications
(59 reference statements)
1
2
0
Order By: Relevance
“…Furthermore, given the large number of CaP-filled macrophages and very low numbers of osteoclasts observed in this current study, it seems that CaP resorption is mainly macrophage-driven. This is consistent with the findings of recent studies which was reported the presence of CaP particles in macrophages after 12, 13, and 52 weeks following implantation in calvarial sheep models of similar CaP composition [28,56,57].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, given the large number of CaP-filled macrophages and very low numbers of osteoclasts observed in this current study, it seems that CaP resorption is mainly macrophage-driven. This is consistent with the findings of recent studies which was reported the presence of CaP particles in macrophages after 12, 13, and 52 weeks following implantation in calvarial sheep models of similar CaP composition [28,56,57].…”
Section: Discussionsupporting
confidence: 93%
“…Depending on their polarization [49] (M1 or M2), macrophages are in fact involved in each phase of the process, i.e. : (1) by cleaning up damaged tissue at the peri-implant area immediately after clot formation [16,50] (2) by initiating tissue reorganization through large enzyme production (3) by inducing [28] bone formation through the secretion of growth hormones such as transforming growth factors, fibroblast growth factors, epithelial growth factors, or also bone morphogenic proteins [48], all involved in recruitment and differentiation of osteogenic cell lines [42,48,51,52] (4) by supporting tissue neovascularization via the secretion of angiogenic molecules [49,50,53,54] and finally (5) by playing a prominent role in the biodegradation of materials [55]. Furthermore, given the large number of CaP-filled macrophages and very low numbers of osteoclasts observed in this current study, it seems that CaP resorption is mainly macrophage-driven.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable presence of osteoblasts has been observed at early and late stages in preclinical models. Interestingly, minimal osteoclast activity was observed [19,20,[46][47][48]; instead, a moderate to substantial presence of material-filled macrophages was observed, which are also responsive to the complement proteins C3a, C5a, and bradykinin [49]. Contrarily, titanium meshes [19], solid titanium implants, and PEEK have been found to trigger a foreign body reaction, leading to chronic inflammation that promotes fibrous encapsulation rather than bone formation [19,25,50].…”
Section: Discussionmentioning
confidence: 99%
“…A macro contact angle meter (DM-CE1, Kyowa, Japan) with appropriate software (FAMAS, Kyowa, Japan) was used to perform the wettability tests and calculate the contact angles. The contact angle (θ) was defined as the angle between the solid phase and the liquid phase as described [20]. Prior to the contact angle experiments all materials were cleaned in water and dried in a desiccator.…”
Section: Wettabilitymentioning
confidence: 99%